Evolving norms of protection: China, Libya and the problem of intervention in armed conflict. Issue 3 (2nd July 2016) - Shesterinina, Anastasia
Abstract: This article examines the influence of civilian protection norms on China's response to the 2011 crisis in Libya. It argues that Responsibility to Protect—an emerging norm commonly associated with the Libyan case—did not play a major role in China's abstention on Resolution 1973 (2011) authorizing international intervention in Libya. For China, Responsibility to Protect is merely a concept and could not serve as the basis for intervention. Instead, Protection of Civilians in Armed Conflict, as a normative foundation for civilian protection endorsed by China, offers a more appropriate lens for understanding China's vote. Protection of Civilians, however, does not accommodate China's unprecedented evacuation of Chinese nationals from Libya. This operation proceeded from a third logic of Protection of Nationals Abroad, which poses dilemmas for China's strict adherence to the principles of sovereignty and non-interference and brings to bear domestic interests and notions of protection.